Acoustic field in the mechanical workshop - Piechowicz, Janusz (Archives of Acoustics, 2007)
Either wave methods or geometric ones are used to describe an acoustic field in industrialhalls. The acoustic field distribution in such halls is not uniform, thus the assumption of fielddiffusivity applied in an acoustics of interiors is often not fulfilled. The room forms amplitudeand phase characteristics of the signal, introducing additionally effects related to spacedevelopment, which are decisive for the acoustic pattern in the observation point. The paperpresents an analysis of an acoustic field inside an industrial room, when one machine ofnot large dimensions is operating. The geometric model of the workshop was implementedand Raynoise software was used to determine the distribution of the sound level for selectedfrequencies. The measurement results and computer simulations related to the acoustic fielddistribution are given.